IMPLEMENTATION OF CASE BASED LEARNING TO IMPROVE HIGHER ORDER THINKING SKILLS (HOTS) OF STUDENTS OF SMAN 1 TILATANG KAMANG - Ihsan Arif Saputra; Nofrion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' critical and analytical thinking skills in analyzing geographical problems are still low due to the dominance of conventional learning methods, such as lectures, which do not give students the opportunity to digest the material deeply. This study aims to determine the effect of Case Based Learning implementation on the improvement of Higher Order Thinking Skills (HOTS) of SMAN 1 Tilatang Kamang students. This research used Quasy Experiment method with quantitative approach and this research design used Pre-test - Post-test Control Group Design. The study population was class X students in the 2024/2025 academic year with a total of 245 students from 7 classes. The research sample consisted of class X.E5 as the control class (34 students) and class X.E3 as the experimental class (33 students) selected using purposive sampling technique. Data collection techniques include observation, documentation, and tests using objective questions according to HOTS categories (analyzing, evaluating, creating, critical thinking, and problem solving). The data were analyzed using IBM SPSS 27 with the N-gain test and T-test. The results showed that the average Pre-test of the experimental class was 43.01 and Post-test was 75.07, while the control class obtained Pre-test 40.13 and Post-test 62.99. There was a significant increase in the experimental class. The Paired Sample T-Test test results show a significance level (sig) of 0.001 because the significance is smaller than 0.05, so Ho is rejected and Ha is accepted. Thus, the application of Case Based Learning has a positive effect on increasing students' HOTS in geography subjects at SMAN 1 Tilatang Kamang, as seen from the learning outcomes and student activities.